Technical note: Improvement of cadaveric skin samples (with severe morphological alteration connected to putrefaction or injury) by an extended histological processing. (April 2016) - Boracchi, M.; Andreola, S.; Gentile, G.; Maghin, F.; Marchesi, M.; Muccino, M.; Zoja, R.
Highlights: A prolonged manual histological processing is proposed. This technique could improve cadaveric skin slides. Injury, putrefactive and processing artefacts are reduced in number. Abstract: Introduction: The microscopic study and the interpretation of skin samples with advanced post-mortal phenomena or with particular destructive injuries is problematic for the forensic pathologist. In an attempt of restoring the histological architecture of cadaveric skin and overcoming these types of problem, the Authors performed a histological processing that was longer than the standard: it was extended until 62 days to evaluate the improvement of the microscopic morphological aspect. Materials and methods: Cutaneous samples were taken from 25 cadavers (5 typologies of skin: charred, putrified, corifed, mummified and partially skeletonized), fixed with a 10%-buffered formalin and then processed in two different ways: one half of the samples was routinely addressed to the standard-time automatic technique, while the other half was manually processed with prolonged times. All the slides were then stained in Hematoxylin–Eosin. Results: The standard-processed slides demonstrated marked morphological alterations and artefacts at the microscopic observation; conversely, those processed with the prolonged manual technique showed an improvement in the morphological structure, sometimes permitting the identification of the anatomical components. Conclusion: Though it is characterized by the inconvenience of protracted times, the application of a long-term manual histological processing to cadaveric skin samples with advanced post-mortal alteration permits to better observe the anatomical architecture of skin and it could be useful and helpful in the evaluation of such cases.